High HPV16 E6 viral load in the oral cavity is associated with an increased number of bacteria: A preliminary study - Shigeishi, Hideo (Biomed Rep, 2018)
In a previous study, the present research group reported that males had a significantly higher prevalence of human papillomavirus (HPV)16 than females in oral rinse samples. The objective of the present study was to examine the relationship between HPV16 viral load and clinical factors, including remaining teeth, denture use and numbers of oral bacteria. A total of 124 patients (48 males and 76 females; mean age, 61.6 years; age range, 20–97 years) who visited the Department of Oral and Maxillofacial Reconstructive Surgery of Hiroshima University Hospital (Hiroshima, Japan) between November 2016 and August 2017 were analyzed. None of the patients had evidence of oral cancer or pre-malignant lesions, including epithelial dysplasia and leukoplakia. Quantitative polymerase chain reaction (qPCR) analysis was employed to examine the number of HPV16 viral copies. Furthermore, the number of oral bacteria was determined using the dielectrophoretic impedance measurement method. HPV16 was below the limit of detection in qPCR findings for samples obtained from 30 of the 124 subjects, thus the association of HPV16 viral copy number with clinical parameters was examined in the remaining 94 patients. The average number of HPV16 E6 DNA copies was 1.65±3.47 copies/cell (range, 0.07–25.3 copies/cell) and was significantly higher in subjects with a high oral bacteria count [≥10(6.5) colony forming unit (CFU)/ml] than in those with a low count (<10(6.5) CFU/ml) (0.79±0.98 vs. 2.06±4.11 copies/cell; P=0.030). The present results indicated that HPV16 viral load may be related to an increased bacterial number in the oral cavity. Further investigations are required to clarify the correlation between oral HPV load and oral hygiene status.